Application of Maggot-based Chitosan for Edible Coating on Cut Papaya (Carica papaya L.) - Sri Wahyuni; Hanaa Ashiilah; Laksmi Ambarsari; Haryo Tejo Prakoso; Siswanto Siswanto (Jurnal Ilmu Pertanian Indonesia, 2026)
Minimally processed papaya fruits are susceptible to postharvest losses due to Colletotrichum sp. infection during storage, necessitating additional postharvest treatments such as putting an edible coating to the surface to minimize microbial growth and weight loss. Exuviae from Hermetia illucens maggots, which are rarely utilized, contain chitin, which can be converted into chitosan. It also possesses antibacterial properties, making it a viable candidate for edible coatings on papaya fruits. There are various approaches for using edible coating processes. Two of these are spray and immersion methods. In this study, the antifungal activity of synthesized chitosan was tested against Colletotrichum sp. and applied as an edible coating to sliced papaya fruit via spray and immersion ways. The effectiveness of the two strategies was compared. The findings revealed that black soldier fly-derived chitosan at varied concentrations (25 to 100 ppm) had antifungal action against the tested fungus. and can be used as an edible coating on sliced papaya fruit. When applied by spray and stored at 10°C, chitosan coating at a concentration of 100 ppm is highly effective in inhibiting Colletotrichum sp. growth and fruit weight loss, extending its shelf life by more than 20 days. Keywords: chitosan, Colletotrichum sp., cut papaya, edible coating